Role of Hypertension and Other Clinical Variables in Prognostication of Patients Presenting to the Emergency Department With Major Bleeding Events. Issue 3 (September 2018) - Conti, Alberto; Molesti, Daniele; Bianchi, Simone; Catarzi, Stefania; Mazzucchelli, Mariuccia; Covelli, Antonella; Tognarelli, Andrea; Perrotta, Mafalda Ester; Pampana, Alessandro; Orlandi, Giovanni; Dell'Amico, Iginio; Baratta, Alberto; et al.
Abstract : Background: Clinical variables including hypertension could be linked with major bleeding events and death beyond vitamin K antagonist (warfarin) or direct oral anti-coagulants (DOACs) treatment strategy. Methods: Subgroup analysis of major bleeding (primary endpoint) associated with clinical variables, site of bleeding, ongoing antithrombotics, reversal treatment or blood transfusion, outcomes (secondary endpoints) was performed in patients with bleeding events submitted to hard 5:1 propensity-score matching for hypertension. Results: Enrolled patients were 2, 792 (mean age, 65.6 ± 19.9 years) during 2-year survey including 166, 000 visits, of 200, 000 inhabitants catchment area; 8, 239 patients received warfarin and 3, 797 DOACs. Hypertension account for 1, 077 (39%) patients; major bleeding for 474 (17%); death for 29 (1%), and 72 (3%) on 1-month and 1-year, respectively. Hypertension, age, glucose, cancer, ischemic vascular disease, and CHA2D2VASc score were more likely to link with major bleeding. On multivariate analysis, only age (odds ratio [OR], 1.02; P < 0.001), CHA2DS2VASc score ≥ 2 (OR, 2.14; P = 0.001), and glucose (OR, 1.01; P = 0.005) were predictors of major bleeding. Kaplan–Meier analysis demonstrated patients with hypertension as compared with patients without showed 60% versus 20% death on 1-month ( P < 0.001). Warfarin compared with DOACs was more likely to present with major bleeding (0.7% versus 0.2%; OR, 2.8; P = 0.005). Receiver operator characteristics analysis showed high value (0.61) of age and glucose over creatinine and systolic arterial pressure ( P = NS). Conclusions: Four in 10 patients with major bleeding showed hypertension; of these 8 in 10 will die within 1 month. Warfarin compared with DOACs was more likely to present with major bleeding.